(untitled) (Forum Penelitian Agro Ekonomi, 2023)
The reduction in the area of agricultural land, coupled with the increase in population, has led to a decline in land tenure per person. The challenge is how to formulate land resource policies so that the reduction in this ratio can still guarantee food security. The purpose of this article is to analyse land resource policies and tenure systems in Indonesia, as well as the role of land consolidation through corporate farming and “farmer corporation” (“korporasi petani”) to achieve economies of scale, efficiency, and added value in agriculture. The analytical method used is a literature review. The analysis results show that the main factors determining the degree of poverty are land ownership and access to land. However, granting farmers access or rights to land alone is not strong enough to increase productivity. Indonesia needs policy instruments that ensure farmers fulfil the farming economies of scale, produce efficiently, and obtain added value. One is by transforming farming institutions that carry out land consolidation in managing farmer corporations to create efficiency and effectiveness in agricultural business. Its implementation includes technical standardisation of cultivation and production quality, ease of supply of inputs and capital, handling of harvest and post-harvest, processing of products and by-products, and marketing.